Serum albumin predicts cardiac adverse events in patients with advanced atherosclerosis – interrelation with traditional cardiovascular risk factors - Schillinger, Martin; Exner, Markus; Mlekusch, Wolfgang; Amighi, Jasmin; Sabeti, Schila; Schlager, Oliver; Wagner, Oswald; Minar, Erich (Thrombosis and Haemostasis, 2004)
Low serum albumin is a powerful predictor of cardiovascular adverse events in healthy subjects and patients with subclinical atherosclerosis. We investigated the association between serum albumin, traditional cardiovascular risk factors, markers of inflammation and cardiovascular outcome in 515 patients with advanced atherosclerosis and severe peripheral artery disease. Cardiovascular risk profile, serum albumin, serum amyloid A (SAA) and fibrinogen were obtained at baseline, and patients were followed for median 21 months (interquartile range 12 to 25) for the occurrence of major adverse cardiac events (MACE: myocardial infarction, percutaneous coronary interventions, coronary artery bypass graft, and death). We observed 135 MACE in 109 patients (21%). Cumulative event-free survival rates at 6, 12, and 24 months were 95%, 91%, and 80%, respectively. Low albumin predicted MACE independently of SAA and fibrinogen. Adjusted hazard ratios for the occurrence of MACE, any death, and the composite of death and MI according to increasing quartiles of albumin were 2.40, 1.14 and 1.09 (p<0.001), 2.94, 1.34 and 1.11 (p=0.003) and 3.63, 1.86 and 1.29 (p<0.001), respectively, as compared to the highest quartile. Considering albumin in conjunction with traditional cardiovascular risk factors (smoking, hyperlipidemia, hypertension and diabetes), we found that low albumin predicted MACE only in patients with a low risk profile (less than 3 risk factors) (p<0.001), whereas low albumin was not associated with MACE in patients with three or more risk factors (p=0.66). We conclude that low serum albumin is associated with cardiovascular outcome of patients with advanced atherosclerosis adding to the prognostic information of other inflammatory markers, and may be particularly useful for risk prediction in patients with few traditional risk factors.
Keywords: Arteriosclerosis; complications; inflammation; albumin